2021
DOI: 10.1002/ame2.12151
|View full text |Cite
|
Sign up to set email alerts
|

Studying host genetic background effects on multimorbidity of intestinal cancer development, type 2 diabetes and obesity in response to oral bacterial infection and high‐fat diet using the collaborative cross (CC) lines

Abstract: Background Multimorbidity of intestinal cancer (IC), type 2 diabetes (T2D) and obesity is a complex set of diseases, affected by environmental and genetic risk factors. High‐fat diet (HFD) and oral bacterial infection play important roles in the etiology of these diseases through inflammation and various biological mechanisms. Methods To study the complexity of this multimorbidity, we used the collaborative cross (CC) mouse genetics reference population. We aimed to study the multimorbidity of IC, T2D, and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Regarding AUC in the early phase after infection (week 6), in both sexes, on CHD, higher blood glucose level was observed in the noninfected group than in the infected group, also proposed by Milhem et al, 52 whereas on HFD, higher blood glucose level was observed in the infected group than in the noninfected group. A positive Δ value indicated a slow glucose tolerance status, which could lead to the conclusion that the infection caused slow and acceleration of diabetes in mice as observed in infection of prediabetic NOD mice, although in type 1 diabetes 53 …”
Section: Discussionsupporting
confidence: 70%
“…Regarding AUC in the early phase after infection (week 6), in both sexes, on CHD, higher blood glucose level was observed in the noninfected group than in the infected group, also proposed by Milhem et al, 52 whereas on HFD, higher blood glucose level was observed in the infected group than in the noninfected group. A positive Δ value indicated a slow glucose tolerance status, which could lead to the conclusion that the infection caused slow and acceleration of diabetes in mice as observed in infection of prediabetic NOD mice, although in type 1 diabetes 53 …”
Section: Discussionsupporting
confidence: 70%
“…However, F. nucleatum also has an anti-inflammatory role through the production of butyric acid ( Stokowa-Soltys et al, 2021 ). Asal Milhen et al found that mice fed a HFD diet had an increased F. nucleatum abundance, with increased body weight and glucose tolerance ( Milhem et al, 2021 ). Another study found a causal link between the activation of the LPS pathway by F. nucleatum and HFD-induced inflammation ( Blasco-Baque et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…123 The strategy for generating system genetics data and pheno- In order to comprehend the pathophysiology, transmission, and host immune response to infection, animal models are essential. 128 Furthermore, the development and testing of medicinal drugs and vaccines depend heavily on animal models. 129 Before choosing an animal model to study an infectious agent, the scientific team must first decide if there is enough ex vivo and in vitro data available to support conducting research into an animal model, if ethical issues are taken care of, and if the data obtained from animal work will contribute meaningfully to the body of scientific knowledge.…”
Section: Modeling P Opul Ation Diver S It Y-the CC Mous E Model For C...mentioning
confidence: 99%
“…In order to comprehend the pathophysiology, transmission, and host immune response to infection, animal models are essential 128 . Furthermore, the development and testing of medicinal drugs and vaccines depend heavily on animal models 129 .…”
Section: Modeling Population Diversity—the CC Mouse Model For Cancer ...mentioning
confidence: 99%